Inducible Nitric Oxide Synthase in the Carcinogenesis of Gastrointestinal Cancers - de Oliveira, Graciele Almeida (Antioxid Redox Signal, 2017)
Significance: Gastrointestinal (GI) cancer taken together constitutes one of the most common cancers worldwide with a broad range of etiological mechanisms. In this review, we have examined the impact of nitric oxide (NO) on the etiology of colon, colorectal, gastric, esophageal, and liver cancers. Recent Advances: Despite differences in etiology, initiation, and progression, chronic inflammation has been shown to be a common element within these cancers showing interactions of numerous pathways. NO generated at the inflammatory site contributes to the initiation and progression of disease. The amount of NO generated, time, and site vary and are an important determinant of the biological effects initiated. Among the nitric oxide synthase enzymes, the inducible isoform has the most diverse range, participating in numerous carcinogenic processes. There is emerging evidence showing that inducible nitric oxide synthase (NOS2) plays a central role in the process of tumor initiation and/or development. Critical Issues: Redox inflammation through NOS2 and cyclooxygenase-2 participates in driving the mechanisms of initiation and progression in GI cancers. Future Directions: Understanding the underlying mechanism involved in NOS2 activation can provide new insights into important prevention and treatment strategies. Antioxid. Redox Signal. 26, 1059–1077.